Implementation of Digital Learning with the Utilization of Photos of Events on Social Media in News Text Materials - Agustina, Fitrianika; Huda, Miftakhul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study analyzes how digital learning—specifically the use of real‑world event photos sourced from social media—can be implemented to teach news‑text composition to seventh‑grade students at SMP Muhammadiyah 1 Surakarta, assessing whether integrating authentic visual stimuli enhances both writing proficiency and 21st‑century digital literacy skills. Methodology: Adopting a qualitative case‑study approach, researchers worked with all 20 students in class VII C. Data sources included observation sheets documenting classroom interactions, students’ written news‑text assignments based on selected photos, and semi‑structured interviews with participants. Data collection combined direct classroom observation, task analysis, and in‑depth interviews, while analysis followed Glaser and Strauss’s constant comparative method to identify emerging themes related to engagement, skill development, and pedagogical effectiveness. Results: Findings indicate that incorporating social‑media event photos into news‑text lessons successfully motivated students and provided concrete anchors for practicing journalistic writing conventions—such as headline crafting, fact‐checking, and narrative structuring. Moreover, students demonstrated growth in digital literacy competencies, including information retrieval, critical evaluation of online sources, and multimedia presentation. Each student group produced a culminating project in the form of an Instagram‑style post, showcasing their ability to synthesize visual and textual information effectively. Applications/Originality/Value: By designing digital learning around authentic social‑media content, this study offers an innovative model for news‑text instruction that aligns with contemporary media practices and technological advancements. Its approach can guide educators in other institutions seeking to modernize language curricula, fostering both writing skills and digital literacy. Furthermore, the research contributes a novel case of leveraging social‑media artifacts as pedagogical tools, illustrating how educational adaptation to evolving science and technology can enrich classroom learning experiences.